1981
DOI: 10.1007/bf00276447
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of glucose phosphate isomerase and phosphoglucomutase in Aedes albopictus (diptera: culicidae)

Abstract: Glucose phosphate isomerase (E.C. 5.3.1.9) and phosphoglucomutase (E.C. 2.7.5.1) were found to be polymorphic in a laboratory colony of Aedes albopictus. The glucose phosphate isomerase locus is represented by two alleles resulting in three genotypes, while the phosphoglucomutase locus is represented by at least five alleles giving rise to a total of 15 genotypes. The inheritance of these two enzymes is of the Mendelian type with codominant alleles. Present data indicate that these genes are not linked.Of 105 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…General experience has shown that laboratory populations of insects and mice, though inbred for many years and strongly selected for homozygosity of any mutant allele affecting coat colour, eye size or wing pattern, nevertheless exhibit polymorphism at blood protein or allozyme loci (Leibenguth, 1972;Pasteur, 1974;Watanabe et al, 1982;Yong et al, 1981). Among the mechanisms maintaining genetic polymorphism, heterosis is thought to be a major factor.…”
Section: Introductionmentioning
confidence: 99%
“…General experience has shown that laboratory populations of insects and mice, though inbred for many years and strongly selected for homozygosity of any mutant allele affecting coat colour, eye size or wing pattern, nevertheless exhibit polymorphism at blood protein or allozyme loci (Leibenguth, 1972;Pasteur, 1974;Watanabe et al, 1982;Yong et al, 1981). Among the mechanisms maintaining genetic polymorphism, heterosis is thought to be a major factor.…”
Section: Introductionmentioning
confidence: 99%
“…albopictus. Tadano et al (1980), Tadano (1981Tadano ( , 1982Tadano ( ,1984Tadano ( ,1987Tadano ( , 1989, and Yong et al (1981) mapped 13 genetic markers (7 visible markers and 6 isozyme loci), and Severson et al (1995a) mapped 18 cDNA markers in Ae. albopictus.…”
mentioning
confidence: 99%
“…Polytene chromosomes have been basic tools for interpreting chromosomal evolution in anopheline mosquitoes and other insects (simulids, chironomids, drosophilids). However, usable polytene chromosomes are not present in most culicine mosquitoes [exceptions are Orthopodomyia (Munstermann et al 1985) and Sa- Munstermann and Craig 1979;Munstermann 1990aTadano 1984, 1987Yong et al 1981Pashley and Rai 1983Matthews and Munstermann 1990Munstermann 1981;Munstermann et al 1982;Munstermann 1990bTadano 1982, 1983aYong et al 1980, 1981Munstermann 1981 bethes (Munstermann and Marchi 1986)]. In the absence of good polytene chromosomes in culicine mosquitoes (Aedes and Culex), enzyme linkage maps have proven especially useful for studying karyotypic evolution.…”
mentioning
confidence: 99%